PREVENTION OF FURTHER PSYCHOSOCIAL DISORDERS OF THE APPLICATION OF THE MODULE OF THERAPY ACTIVITIES IN THE SENSORY STIMULATION GROUP - Yanni Karundeng; Maykel A. Kiling (POLTEKKES KEMENKES MANADO, 2018)
Background: The process of aging in the course of human life is a natural thing that will be experienced by all those who are blessed with long life, only the speed of the process depends on the individual concerned. Individually, the natural aging process occurs. This will cause physical, mental, social, economic and psychological problems. Psychological problems that occur in the elderly one of which is psychosocial disorders such as dependence on others, isolate themselves or withdraw from social activities. clients who do not want to express verbal communication will be stimulated emotions and feelings, and display responses, providing sensory stimulation group activity therapy. Aims : to determine the effect of sensory stimulation group activity therapy on elderly psychosocial disorders. Method: This research uses a quasi-experimental design: Non equivalent control group design with a sampling technique that is purposive sampling of 20 respondents divided into 10 elderly for the experimental group and 10 elderly for the control group. Data collection techniques through observation and interviews. Results: there is a difference in the p value of the experimental group and the control group, where in the experimental group the price of p = 0,000 is less than 0.05 and in the control group p = 0.317. Conclusion: this shows that there is a therapeutic effect of sensory stimulation group activity on picosocial disorders in the intervention group. Whereas in the control group who were not given therapeutic activity the sensory stimulation group had no chance of experiencing a decrease in psychological disorders.